A framework for understanding the critical success factors of enterprise business intelligence implementation - Mungree, D.; Rudra, Amit; Morien, Diane (AISEL, 2013)
Implementation of a business intelligence (BI) system requires considerable resources. Although, the BI market appears vibrant and the importance of BI is widely accepted, few studies have investigated the Critical Success Factors (CSF) that affects its successful implementation. There is an imperative for a CSF approach to enable BI stakeholders to focus on the key issues that lead to successful BI systems implementation. This paper investigates the success factors and their contextual issues that may help organizations achieve a successful BI system implementation.